Odpowiedzi

  • Użytkownik Zadane
2010-01-27T13:05:57+01:00
A.
x²=18
x=√18
b2x²-1=17
2x²=18
x²=9
x=3
c)
6x² - 1 i 3/5=0
x²=8/30
x=√ 8/30
d)
-2x²-x²=5-1
-3x²=4
x²=-4/3
(równanie sprzeczne)
e)
-3x²=-12
x²=4
x=2
f
.7x²=8
x²=8/7
x=√8/7
g
.4x²+8=8
4x²=0
x=0
h
5+x²=0
x²=5
x=√ 5
i
.9/2 - 3x²/6=1-2x²/2
27-3x²=3-6x²
-3x²+6x²=3-27
3x²=-24
x²=-8
( równanie sprzeczne)
  • Fao
  • Rozwiązujący
2010-01-27T13:23:51+01:00
A) 1/2x² = 9 / ×2
x² = 18
x = √18

b) 2x²-1=17 / +1
2x² = 18
x² = 9
x = 3

c) 6x² - 1 i 3/5=0 / + 1 i 3/5
6x² = 1 i 3/5
6x² = 8/5 / :6
x² = 4/15
x = 2/√15
x = 2√15/15

d)1-2x²=5+x² /-1
-2x² = 4 + x² / -x²
-3x² = 4 /:(-3)
x² = - 4/3
x = - 2/√3
x= - 2√3/3

e)12-3x²=0 / - 12
-3x² = -12 / :(-3)
x² = 4
x = 2

f)6x²=8-x² / - x²
5x² = 8 /:5
x² = 8/5
x = √8/√5
x = √40/5
x = 2√10/5

g)4(x²+2)=8
4x² + 8 = 8 /-8
4x² = 0
x² = 0
x = 0

h)5+x²/2 -4=0 /+4 , -5
x²/2 = -1 / ×2
x² = -2
x = -√2

i)3(1 i 1/2 - x²/6)=1-2x²/2 /×2
6(1 i 1/2 - x²/6) = 1-2x²
9 + x² = 1 - 2x² /-9 ; +2x²
3x² = -8
x² = -8/3
x = - √8/√3
x = - √24/3
x= - 2√6/3









Najlepsza Odpowiedź!
2010-01-27T13:29:00+01:00
1.
a) 1/2x²=9 / *2x²
1=9*2x² / :9
1/9 = 2x² / :2
1/18 = x² / *pierwiastek
x = pierwiastek z 1/18

b) 2x²-1=17
2x²=18 / :2
x² = 9 / * pierwiastek
x = pierwiastek z 9
x = 3

c) 6x² -1 i 3/5= 0
6x² = 1 i 3/5 / :6
x² = 4/15 / * pierwiastek
x = pierwiastek z 4/15

d) 1-2x²=5+x²
3x²=4 / :3
x² = 4/3 / * pierwiastek
x = pierwiastek z 4/3

e) 12-3x²=0
-3x²=-12 / :(-3)
x²=4 / * pierwiastek
x=pierwiastek z 4
x=2

f)6x²=8-x²
7x²=8 / : 7
x²=8/7 / * pierwiastek
x=pierwiastek z 8/7

g)4(x²+2)=8
4x²+8=8
4x²=0
x=0

h)5+x²/2 -4=0 / *2 ciężko się domyślić jak to właściwie wygląda
5+x²-8=0
x²=3 / * pierwiastek
x=pierwiastek z 3

i)3(1 i 1/2 - x²/6)=1-2x²/2
9/2 - x²/2 = 1-2x²/2 /*2
9-x²=2-2x²
x²=-7 / * pierwiastek
x=pierwiastek z -7 (nie może być z minusowej liczby)
x=brak rozwiązań